Evaluation the Effect of Laminated Layer Sequence of Plain-Woven Bamboo on Tensile and Impact Performance of E-glass Woven / Epoxy Hybrid Composites - Rassiah, Kannan; Ali, Aidy; Saeman, Muhadir (International Journal of Integrated Engineering, 2021)
Bamboo reinforced hybrid composites are needed in claim to progress use of polymer composite technology. This paper describes a hand lay-up laminate process using plain-woven bamboo/E-glass woven/epoxy hybrid composite with the Design of experiment (DOE) 2 factor with 3- level and analysis of variance (ANOVA) was implemented for an evaluation against how the bamboo and e-glass woven affect the mechanical properties of hybrid composite in various sequence. The present study considers influence of plain-woven bamboo and e-glass woven laminated hybrid composite towards its tensile and charpy impact test performance. The results show that the 2-layer composites withstood better tensile strengths 185.372 MPa for EG/BW/EG while charpy impact 158.224 KJ/m2 for EG/BW sequence respectively. Experiments results show that concentrate on both lay-up sequence and layers are important effect factors for tensile and charpy performance. It had been proven that both the layers and also the lay-up sequence demonstrated significantly different leads to terms of the mechanical performance.